2015
DOI: 10.1071/fp15057
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of photosynthesis within leaves is associated with alteration of leaf structural features and leaf N content per leaf area in rice

Abstract: Increasing leaf photosynthesis rate (A) is considered an important strategy to increase C 3 crop yields. Leaf A is usually represented by point measurements, but A varies within each leaf, especially within large leaves. However, little is known about the effect of heterogeneity of A within leaves on rice performance. Here we investigated the changes in gas-exchange parameters and leaf structural and chemical features along leaf blades in two rice cultivars. Stomatal and mesophyll conductance as well as leaf n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 44 publications
1
32
1
Order By: Relevance
“…S4. An earlier study found that K leaf was linearly correlated with g s across the selected genotypes (R 2 = 0.57, P = 0.007; Xiong et al, 2015c), but the present study found no relationship between g s and either K x or K ox individually (Fig. S4).…”
Section: Leaf Venation and Stomatal Features On K Leafcontrasting
confidence: 81%
See 2 more Smart Citations
“…S4. An earlier study found that K leaf was linearly correlated with g s across the selected genotypes (R 2 = 0.57, P = 0.007; Xiong et al, 2015c), but the present study found no relationship between g s and either K x or K ox individually (Fig. S4).…”
Section: Leaf Venation and Stomatal Features On K Leafcontrasting
confidence: 81%
“…Water transport and CO 2 diffusion inside leaves are two important functional traits that determine the CO 2 assimilation efficiency (Sack & Holbrook, ; Flexas et al ., ). In our previous study (Xiong et al ., ), we found that both leaf hydraulic conductance ( K leaf ) and mesophyll conductance ( g m ) varied widely among Oryza genotypes, and showed a large degree of correlation with one another. In the current study, our detailed examination of leaf functional and anatomical features provides new insight into the variation of K leaf and g m across related genotypes and their correlations.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…CO 2 conductance includes stomatal conductance ( g s ) and mesophyll conductance ( g m ) (Grassi and Magnani , DaMatta et al ). Increasing leaf N content is beneficial for increasing g s and g m and stimulating CO 2 conductance (Xiong et al ). The AtNRT1.1 nitrate transporter of Arabidopsis thaliana (Arabidopsis) supports stomatal function by adjusting the nitrate concentration in guard cells (Guo et al ).…”
Section: Introductionmentioning
confidence: 99%
“…2a); however, it has been reported that the chlorophyll concentration in the palisade tissue is higher than that in the spongy tissue (Terashima and Saeki, 1983; Cui et al , 1991), and that the chlorophyll content is highly heterogeneous along the leaves (Xiong et al , 2015). Therefore we also examined the effect of variation in chlorophyll concentration between palisade and spongy chloroplasts on the internal light environment.…”
Section: Methodsmentioning
confidence: 99%